Combination therapies for COVID‐19: An overview of the clinical trials landscape. Issue 4 (17th October 2021) - Akinbolade, Sola; Coughlan, Diarmuid; Fairbairn, Ross; McConkey, Glenn; Powell, Helen; Ogunbayo, Dapo; Craig, Dawn
Abstract : The COVID‐19 pandemic has driven an unprecedented level of global activity in drug discovery and clinical development for effective therapeutics targeting the coronavirus disease. There are currently 744 therapeutics being tested in 2879 clinical trials globally. Almost 90% of these clinical trials are focused on monotherapies. Combination therapies are the mainstay of antiviral therapeutics to increase the potency of the individual compounds and to combat the rapid evolution of resistance, although combination therapies have inherently complex clinical and regulatory development challenges. Increased understanding of the SARS‐CoV‐2 lifecycle and COVID‐19 pathology provides a scientific rationale for evaluating the effectiveness of different combinations. In this paper, we provide an overview of the current clinical trial landscape for combination therapeutics targeting COVID‐19 through weekly scanning of national and international clinical trial registries. Our analysis delves specifically into dual combination therapies in what can be defined as "pivotal clinical trials" (active, randomised, controlled and at least phase II), with a focus on new and repurposed therapeutic candidates that have shown positive signals and/or been granted authorisation for emergency use based on positive efficacy and safety data.